2011
DOI: 10.1016/j.athoracsur.2011.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of FDG-PET to Diagnose Lung Cancer in a Region of Endemic Granulomatous Disease

Abstract: Background 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) is used to evaluate suspicious pulmonary lesions due to its diagnostic accuracy. The southeastern United States has a high prevalence of infectious granulomatous lung disease, and the accuracy of FDGPET may be reduced in this population. We examined the diagnostic accuracy of FDG-PET in patients with known or suspected NSCLC treated at our institution. Methods 279 patients identified through our prospective database, underwent an opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 26 publications
4
76
0
Order By: Relevance
“…The lower specificity of PET-CT in the study by Deppen et al (sensitivity 89%, specificity 40%) was caused by the fact that many examined patients had pulmonary granulomas, which increased the number of false positive results [5]. Nomori et al showed lower sensitivity of PET-CT (38%) because their study also concerned ground-glass opacity lesions (established on computed tomography), which corresponded to neoplastic foci with little marker uptake [6].…”
Section: Discussionmentioning
confidence: 86%
“…The lower specificity of PET-CT in the study by Deppen et al (sensitivity 89%, specificity 40%) was caused by the fact that many examined patients had pulmonary granulomas, which increased the number of false positive results [5]. Nomori et al showed lower sensitivity of PET-CT (38%) because their study also concerned ground-glass opacity lesions (established on computed tomography), which corresponded to neoplastic foci with little marker uptake [6].…”
Section: Discussionmentioning
confidence: 86%
“…2). 18 F-FDG is the most routinely used radiolabeled compound for PET imaging [25,26]. Cells experiencing high glycolytic activities phosphorylate FDG.…”
Section: Imaging and Lung Cancermentioning
confidence: 99%
“…In patients with a history of cancer, a rate of up to 90% malignancy in newly detected SPL has been reported [3]. Currently, positron emission tomography (PET) [4] is the most specific radio-diagnostic tool, but false-positive results in nonmalignant pulmonary lesions such as inflammatory lesions and granulomatous diseases limit its clinical value [5,6,7]. However, histologic proof of SPL should be standard prior to any treatment.…”
Section: Introductionmentioning
confidence: 99%